INTEGRATING POLICY, SDGs, AND BEHAVIOR CHANGE FOR STUNTING CONTROL - Handayani, Wahyu Fitri; Hanida, Rozidateno Putri; Zaim, Muhammad Refo Baqirdin; Daulay, Taufiq Akbar (Jurnal Governansi, 2025)
Indonesia is committed to achieving Sustainable Development Goals (SDGs), especially the second and third goals, child health and nutrition are very important. Stunting is a problem that often occurs in Indonesia. The prevalence of stunting in West Sumatra in 2022 still touched 25.2%, still high from Indonesia's target of 14%. This scientific paper analyzes various relevant literature with descriptive qualitative methods. The AGIL Framework approach by Talcott Parsons found that policy success depends on adaptation to community conditions, achieving clear targets, cross-sector integration, and long-term behavior change. Policies or programs in reducing the prevalence of stunting affect people's attitudes, awareness, and parenting of health and nutrition in children. Based on the analysis conducted, efforts to prevent and manage stunting in West Sumatra have shown changes in community behavior. Programs that are in line with policy directions, such as routine posyandu programs, actions to report children indicated as stunted, Supplementary Food Provision (PMT), and the establishment of Healthy Village Houses (RDS), behavior change communication policies, and specific nutrition interventions, in children aged 0-23 months and pregnant women, have proven effective in influencing changes in community behavior. Therefore, it is hoped that the government can provide support and collaboration between stakeholders, and help increase community participation in controlling the prevalence of stunting in West Sumatra.